IoT based guided fire fighting vehicle - Raafeek, A.R.M.; Satheeskanth, N.; Joy Mathavan, J.; Kunaraj, A. (IOP Publishing, 2022)
Fire accidents are occurring frequently nowadays in domestic and industrial environments with unpredictable climatic changes and human negligence. The proposed prototype is designed to detect such fire accidents and to extinguish the fire by remote operation of the user, and thereby reducing the risk of fire fighters involved. The movement of the vehicle is dictated by the combination of sensor-based inputs and user guidance. When the fire is detected by the fire detection sensor, the signal is immediately passed to the controller. GSM modules will be activated alerting the user about the fire accident. Once the alert is received, the user can guide the vehicle to the required location with the help of Blynk software & in-built camera module to extinguish the fire. The servo motor connected with the firefighting hose can control the direction and volume of water to be sprayed. The controls of the servo motors are with the user. The proposed firefighting vehicle is designed to function using Internet of Things (IoT), thereby enabling the user to control the fire from anywhere.
Keywords: ESP32 cam; Arduino; Flame sensor; IoT; Blynk software; Guided vehicle; Fire hazard